Penerapan Tema Arsitektur Tropis pada Bangunan Pusat Kecantikan di Badung - Soka, Ni Made Ariyana Renawati; Saraswati, Anak Agung Ayu Oka; Swanendri, Ni Made (Jurnal Arsitektur Universitas Udayana; Vol 9 No 02 (2021): Jurnal Arsitektur, Universitas UdayanaDO - 10.24843/jaunud.v9i02.66210, 2021)
Looking physically beautiful is important for modern women and even the awareness of beauty such as body, face, and hair has progressed rapidly. Various beauty services to be available separately, thus a special space is needed in the same area to carry out treatments from hair to toe to save time. This study aimed to design a beauty center building with a tropical architectural approach, thus building users feel comfortable. The method used is a combination of research methods and design methods. The location of this beauty center design is situated in a tropical climate which can have a significant influence on temperature, rainfall, wind, humidity, and solar radiation that affect the building design. Starting from its location, this beauty center design applies a tropical architectural theme that can provide design solutions to the designed building. This theme is applied to the design, including on-site processing, the appearance of the building and spaces in salons, spas, and clinics. With this theme the building is able to respond to the tropical climates such as solar radiation, high rainfall, airflow through the building, thus it can give comfort inside and outside of the building for its users. Besides that, it can preserve nature because this theme is one with nature, not destroying nature. Keywords: beauty, tropical architecture, comfort